Civil Society Actors and the Welfare State. A historically-based analytical framework - Busso, Sandro; De Luigi, Nicola (PARTECIPAZIONE E CONFLITTO, 2019)
Civil society actors have always been crucial players in the development of welfare systems. Far before the appearance of the welfare state, the provision of services to those in need was the domain of charities and guilds, and later on of the mutual aid organizations related to the labour movement. To-gether with providing services, civil society actors have exerted political pressure on the state, demanding an enlargement of social rights or challenging the principles of public intervention. Such a relevant role became even more pivotal after the ’70s, when the welfare mix model paved the way for the entrance of third sector organizations into public service provision and governance processes. Within this scenario, this article aims to develop a historically-based conceptual framework, through which the huge heterogeneity of civil society actors and functions can be analyzed. The possibility of performing several roles represents an opportunity for civil society actors, but at the same times engenders contradictions and trade-offs for social movements and the third sector.